On the Rule of Law of the State's Obligation to Supply for the Basic Medical Security Right in China - Gong, Chenhang (Wonkwang University Legal Research Institute, 2024)
The implementation of the “Healthy China Strategy” is an important part of the current national basic strategy. Health is also related to the basic survival and development of citizens. The right to health is an important fundamental right of citizens, and the basic medical security right is an important part of it. The basic medical security right is the right to guarantee citizens' basic access to medical care and the right to basic medical services, and is closely related to the right to life, the right to health and the right to social security. The State's obligation to supply for the basic medical security right mainly consists of the material supply obligation and the procedural supply obligation: the material supply obligation may be specific to the supply of medical insurance, medical assistance and medical facilities; and the procedural supply obligation consists of the supply of medical service and medical relief. The State's obligation to supply for the basic medical security right in practice in China mainly faces such practical problems as inadequate legal norms and low hierarchy of legislation, large differences in supply among regions, and low level of supply. In this context, the State's obligation to supply for the basic medical security right should be further improved by, among other things, establishing the legal system of supply governed by the Constitution, formulating scientific supply standards, and developing diversified relief channels. At the same time, in terms of the leading and consistent internal logic, change the logic of legislative thinking from emphasizing the medical security administration in “drafts for comments” to the structured and typified basic medical insurance legal relations, establishing the system of medical security law, and thus promote the rule of law of the basic medical security right.